Necessity, Feasibility and Limitation of ESG Investment of Pension Funds in China - Keya Ding (Law and Economy, 2022)
In recent years, green and low-carbon economy has become the main melody of contemporary economic and social development. The proposal of “double carbon” goal promotes the further development of ESG investment concept in China. At the same time, under the influence of COVID-19, people are aware of the importance of sustainable development. ESG investment has become a new hot topic. Pension fund and ESG investment have natural adaptability, and their investment ideas are highly consistent. However, the ESG investment of pension fund in China is still limited by the lack of unified ESG rating system and information disclosure system, the potential profit-seeking tendency of pension fund investment and the lack of professional ESG investment talents. China should actively learn relevant experience from abroad and form an ESG investment model of pension fund in line with its national conditions.